Proton conductivity of multifunctional metal phosphonate frameworks - Cabeza-Díaz, Aurelio; Bazaga-García, Montse; Pérez-Colodrero, Rosario Mercedes; Papadaki, M.; Olivera-Pastor, Pascual; Losilla, Enrique R.; León-Reina, Laura; Moreno-Real, Laureano; García-Aranda, Miguel Ángel; Demadis, Konstantinos D. (My University, 2015)
Metal phosphonates exhibit attractive characteristics for proton conductivity, such as tunable functionality, chemical and thermal stability and the existence of H-bond networks with acidic protons within their structure.1 In the present work, we examine the relationship between crystal structure and proton conductivity for several metal (mono-, di- and tri-valent) phosphonates containing rigid: (5-(dihydroxyphosphoryl)isophthalic acid, PiPhtA and 2-hydroxyphosphonoacetic acid, HPAA) or flexible: (hexa- or octamethylenediamine-N,N,N′,N′-tetrakis(methylenephosphonic acid, H8HDTMP or H8ODTMP) multifunctional ligands. The crystalline hybrid derivatives prepared show a great structural diversity, from 1D to 3D open-frameworks possessing hydrogen-bonded water molecules and phosphonic and carboxylic acid groups. The rigid 3D framework of Ca-PiPhtA, that exhibits a proton conductivity of 5.7•10-4 S/cm as synthesized, transforms into a layered compound upon exposure to ammonia vapors2 with increased proton conductivity (6.6•10-3 S/cm). The flexible frameworks of magnesium or lanthanide phosphonates, with 1D channels, present conductivities higher than 10-3 S/cm. Their activation energies fall in the range corresponding to a Grotthuss mechanism.3,4 For M(I)-HPAA solids conductivities up to 5.6•10-3 S/cm were measured. References 1. P. Ramaswamy, N.E. Wong, G.K.H. Shimizu, Chem. Soc. Rev. 43 (2014) 5913. 2. M. Bazaga-García, R.M.P. Colodrero, M. Papadaki, P. Garczarek, J. Zoń, P. Olivera-Pastor, E.R. Losilla, L. León-Reina, M.A.G. Aranda, D. Choquesillo-Lazarte, K.D. Demadis, A. Cabeza, J. Amer. Chem. Soc. 136 (2014) 5731. 3. R.M.P. Colodrero, P. Olivera-Pastor, E.R. Losilla, D. Hernández-Alonso, M.A.G. Aranda, L. Leon-Reina, J. Rius, K.D. Demadis, B. Moreau, D. Villemin, M. Palomino, F. Rey, A. Cabeza, Inorg. Chem. 51 (2012) 7689. 4. R.M.P. Colodrero, P. Olivera-Pastor, E.R. Losilla, M.A.G. Aranda, L. Leon-Reina, M. Papadaki, A.C. McKinlay, R.E. Morris, K.D. Demadis, A. Cabeza, Dalton Trans. 41 (2012) 4045.
Keywords: Compuestos metálicos; Proton conductivity; MOFs; Hybrid materials; Metal phosphonates